VITAMIN D DEFICIENCY IN WOMEN WITH VAGINAL DISCHARGE - Rakhmatullaeva M.M; Sharipova Sh.U (Scholar Express Journals, 2022)
The results of the study of D-vitamin status in women with bacterial vaginosis are presented. It was revealed that the increase in vitamin D deficiency is associated with the aggravation of vaginal dysbiosis. Given these data, it can be assumed that vitamin D deficiency is an additional risk factor for the development of bacterial vaginosis
Keywords: bacterial vaginosis; vitamin; D-deficiency